Psychomotor therapy as a treatment of chronic spinal pain: A qualitative study - Claudia Véron; Stéphane Genevay; Maud Knafou Bastard; Adrien Fleury; Christine Cedraschi (Elsevier, 2021)
Objective: Psychomotor therapy is an innovative complementary approach that enhances the mind-body connection. It could have a positive effect on chronic pain syndromes but has not yet been specifically studied for spinal pain. We thus aimed to explore the experiences of chronic spinal pain patients with psychomotor therapy. Design: We conducted a qualitative study using semi-structured interviews. 17 patients with chronic spinal pain were recruited from a multidisciplinary spinal pain program in a rehabilitation hospital in Switzerland. Participants received psychomotor therapy as part of this care. All interviews were transcribed and thematic analysis was performed. Setting: Division of General Medical Rehabilitation, Geneva University Hospitals, Geneva, Switzerland. Results: Four themes emerged from thematic analysis: 1) Connecting body and mind; 2) Passive individualized care; 3) Effect on mobility and well-being versus pain; and 4) Need for further care. Participants particularly appreciated the person-centered approach, relaxation and link between body and mind in the psychomotor therapy sessions. They shared positive effects of psychomotor therapy on mobility, kinesiophobia and overall well-being, rather than on pain. Finally, they would have liked more follow-up care at the end of the program. Conclusions: Experiences reported by patients in this study suggest that psychomotor therapy could be a promising complementary therapy for chronic spinal pain within a biopsychosocial approach. To better understand the benefits of psychomotor therapy for chronic spinal pain, further research is needed and should consider patient-reported outcome measures such as well-being, fear-avoidance belief and disability.